منهج الإمام الحافظ ابن كثير في فضائل القرآن الكريم - الشهراني، خالد بن محمد بن صالح بن زريق (جامعة طيبة - كلية الآداب والعلوم الإنسانية, 2023)
عنوان البحث: (منهج الإمام الحافظ ابن كثير -رحمه الله- في فضائل القرآن الكريم)، يشتمل هذا البحث على مقدمة، وتمهيد ومبحثين، وخاتمة، وفهارس علمية، المقدمة، وفيها: أهمية الموضوع، وأسباب اختياره، وأهداف البحث، والدراسات السابقة، وحدود الدراسة، وهيكل البحث، والتمهيد، وفيه تعريف المنهج وفضائل القرآن وترجمة موجزة عن الإمام ابن كثير وتفسيره، المبحث الأول: أهمية معرفة فضائل القرآن الكريم، والمبحث الثاني: منهج الإمام ابن كثير في فضائل القرآن الكريم، والخاتمة، وفيها أن معنى المنهج في اللغة هو: الطريق الواضح المستقيم، وفي الاصطلاح هو: مجموع القواعد العامة، والخطوات والقوانين المنظمة التي تحكم عمليات العقل من خلال البحث والنظر في مجال معين، والمقصود بمنهج المفسر هو: طريقته وطريقه للكشف عن حقائق ودلالات ألفاظ القرآن المجيد، وأن معنى الفضل في اللغة هو: الزيادة والبقية، وفي الاصطلاح هو: كون معلوم ما منفردا بصفة مدح أو بمزية في صفة مدح والتفضيل على ضربين عقلي ووضعي، ويقصد بفضائل القرآن ما يشمل الحديث عن فضله على وجه العموم، وعن فضل بعض سوره وآياته، كما اتضح لي أن لمعرفة فضائل القرآن الكريم أهمية عظمى في الإسلام؛ حيث يحفز ذلك المسلم إلى الاهتمام بكتاب الله تلاوة وتدبرا، ولهذا اهتم بها العلماء ومنهم الإمام ابن كثير بها كثيرا في تفسيره اهتماما بالغا، وأن الراجح في مسألة: (هل في القرآن فاضل ومفضول؟) هو القول بالتفضيل، وأن تفسير ابن كثير يعتبر مصدرا من مصادر التفسير بالمأثور، وأنه جمع فيه أكثر ما ورد في فضائل القرآن الكريم، وأن منهج الحافظ ابن كثير فيه منهج دقيق ومهم لكل مفسر، وتبين لي مكانة الإمام ابن كثير في التفسير وعلوم القرآن والحديث، ومكانة تفسيره، وأن منهجه في فضائل القرآن منهج دقيق ومتميز؛ حيث استخدم فيه أنواع فضائل القرآن الثلاثة، وذكر ما ورد في فضل كل سورة قبل البدء في تفسيرها، وكما أوصى في ختام هذا البحث إخواني الباحثين بالاهتمام ببيان فضائل القرآن الكريم وتوضيح مناهج العلماء في ذلك؛ ليكون ذلك حافزا للناس على كتاب الله بتلاوته وتدبره وتطبيق أحكامه. research title: (The methodology of Imam Ibn Katheer- may God have mercy upon him - in the virtues of the Holy Quran (This research includes an introduction, a preface, and three topics, a conclusion, and scientific indexes, the introduction, and includes: the importance of the topic, the reasons for choosing it, the objectives of the research, the previous studies, the limits of the study, the research methodology, the structure of the research, and the preface, and it includes a statement, the concept of curriculum and virtues linguistically and idiomatically, and the first topic: explaining the importance of knowing the virtues of the Holy Qur’an, the second topic: explaining the nation's need to renew knowledge of the virtues of the Holy Quran, and the third topic: The approach of Imam Ibn Katheer, the virtues of the Holy Qur’an. The conclusion, in which the meaning of the method in the language is: the way that is clear and straight, and in the convention is: the sum of the general rules, the steps and the regulating laws that control the operations of the mind through research and consideration in a specific field, and what is meant by the method of the interpreter is: His method and way for revealing the facts and connotations of the words of the Glorious Qur’an, and an explanation of the meanings of the verses, one meaning of virtue in the language is: the increase and the rest, and in the terminology it is: the fact that something is known on its own in the capacity of praise or with an advantage in the adjective of praise and preference over two strikes, my mind and my situation, and the meaning of my mind is that the virtue of the one who is endowed with virtue. The meaning of the positivist is that the superiority of the one who is characterized by it is not due to its rationality, but rather to a wave other than that which has its peak. The meaning of virtues of the Qur’an is what includes talking about its virtue in general, and about the virtue of some its surahs and verses, and the knowledge of the virtues of the Holy Qur’an is of great importance in Islam; as that motivates the Muslim to interest in the Book of God, recitation and contemplation, and for this reason scholars, including Imam Ibn Katheer, paid great attention to it his interpretation is of great interest, and he has a precise methodology in that, and the most correct one is in the question: (Is there any virtuous and favored in the Qur’an? It is the saying of preference, as shown by the position of Imam Ibn Katheer in interpretation and the sciences of the Qur’an and the position of its interpretation.
Keywords: فضائل القرآن -- ابن كثير، إسماعيل بن عمر، ت. 774 هـ. -- التفسيرات القرآنية